„Obecność” średniowiecza w kształceniu studentów wydziałów prawa - Karol Dąbrowski (Czasopismo Prawno-Historyczne)
The subject matter of the Middle Ages is permanently present in the education of law students in Poland. It appears during the following classes: the history of Polish law, the general history of law, the history of political and legal doctrines. The medieval tradition can be inspiring for logicians and methodologists of science. The students of administration and internal security also better understand contemporary legal institutions if they are compared with examples from the Middle Ages.